EKC and carbon footprint of cross-border waste transfer: Evidence from 134 countries - Yi Liu (Elsevier, 2021)
Many developing countries, such as China, Malaysia, Vietnam, India, etc., choose to prohibit waste import. Does this mean the inflection point of the Environmental Kuznets Curve (EKC) in these countries has arrived? In this paper, we first calculate the carbon dioxide emission and energy consumption in major resource-based wastes of 134 countries using the Life Cycle Assessment (LCA) method. Second, we test whether the relationship between CO2 (energy consumption) and GDP per capita confirms an EKC's inverted U-shaped curve. Empirical results show that: (1) the relationship between embodied CO2 emissions (energy consumption) of imported wastes and GDP per capita of a country confirms EKC in various robustness checks, including using an alternative, dependent variable and using sub-sample data. (2) The EKC's inflection point on the average embodied carbon dioxide emissions of imported wastes is 36623.88 USD (37181.3 USD for energy). (3) EKC appears in 68 countries out of 134 countries. Most of these 68 countries have crossed the turning point. This research is novel in describing the EKC of waste trade's carbon footprint using the LCA model. This is the first research that provides empirical evidence to the “Waste Haven Hypothesis”. This result empirically explains the evolution of the global waste trade network. That is, waste first transfers from the “North” to the “South” (from US to Europe, and from Europe to Japan and Korea), and then it moves again from the “South” to the “South” (from China to other Asian countries). It reflects the evolution of global pollution haven transfer in the pollution-intensitive sector. Previous research failed to do it because the indicators used for waste transfer limits to trade value (weight) that can not correctly measure waste transfer's environmental pollution. An advantage of using LCA is that it better estimates the pollution generated by the recycling sectors.